Mastery learning improves simulated central venous catheter insertion by emergency medicine teaching faculty - Pokrajac, Nicholas; Schertzer, Kimberly; Roszczynialski, Kelly N.; Rider, Ashley; Williams, Sarah R.; Poffenberger, Cori M.; Gisondi, Michael A. (AEM education and training, 2021)
Objectives Routine competency assessments of procedure skills, such as central venous catheter (CVC) insertion, do not occur beyond residency training. Evidence suggests variable, suboptimal attending physician procedure skills. Our study aimed to assess CVC insertion skill by academic emergency physicians, determine whether a simulation‐based mastery learning (SBML) intervention improves performance and investigate for variables that predict competence. Methods This is a pretest–posttest study that evaluated simulated CVC insertion by emergency medicine (EM) faculty physicians. We assessed 44 volunteer participants at a large academic medical center over a 1‐month period using a published 29‐item checklist. Our primary outcome was the difference in assessment score before and after a SBML intervention. A secondary analysis evaluated predictors of pretest performance. Results A total of 44 subjects participated. Only four of 44 (9.1%) of subjects met a predefined minimum passing score on pretest. Mean assessment scores increased by 21.5% following the SBML intervention (95% confidence interval [CI] of the difference = 18.1% to 24.8%, p < 0.001). In a regression model, pretest scores increased by 10.8% (95% CI = 2.9 to 18.7%, p = 0.009) if subjects completed postgraduate training within 5 years. Frequency of CVC insertion did not predict performance, but 25 of 44 (56.8%) faculty members had no documented performance or supervision of a CVC insertion within 1 year of assessment. Conclusions SBML is a promising method to assess and improve CVC insertion performance by EM faculty physicians. Recent completion of postgraduate training was a significant predictor of CVC insertion performance. Our results require validation in larger cohorts of EM physicians across other academic institutions.